Multiple Pathways for Homologous Recombination in Saccharomyces Cerevisiae - Rattray, A. J. (1995)
The genes in the RAD52 epistasis group of Saccharomyces cerevisiae are necessary for most mitotic and meiotic recombination events. Using an intrachromosomal inverted-repeat assay, we previously demonstrated that mitotic recombination of this substrate is dependent upon the RAD52 gene. In the present study the requirement for other genes in this epistasis group for recombination of inverted repeats has been analyzed, and double and triple mutant strains were examined for their epistatic relationships. The majority of recombination events are mediated by a RAD51-dependent pathway, where the RAD54, RAD55 and RAD57 genes function downstream of RAD51. Cells mutated in RAD55 or RAD57 as well as double mutants are cold-sensitive for inverted-repeat recombination, whereas a rad51 rad55 rad57 triple mutant is not. The RAD1 gene is not required for inverted-repeat recombination but is able to process spontaneous DNA lesions to produce recombinant products in the absence of RAD51. Furthermore, there is still considerably more recombination in rad1 rad51 mutants than in rad52 mutants, indicating the presence of another, as yet unidentified, recombination pathway.